2008
DOI: 10.1179/174313208x289615
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin protects rat brain through overexpression of HSP70 and reducing brain edema after cerebral focal ischemia

Abstract: GA protects brain from focal ischemia and reduces edema. This may be due, at least in part, to GA overexpression of HSP70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…In contrast to these findings, several groups including ours have found that 17AAG favors cell survival when treated transiently or with lower doses (Koga et al 2006, Kwon et al 2008, Wang et al 2011, Wen et al 2008, Yano et al 2008. Nonetheless, 17AAG's function in stroke has not been studied although its toxic precursor, geldanamycin, exerts beneficial effects in animal stroke models (Kwon et al 2008, Wen, Li, Zong, Yu et al 2013.…”
Section: Introductionmentioning
confidence: 80%
“…In contrast to these findings, several groups including ours have found that 17AAG favors cell survival when treated transiently or with lower doses (Koga et al 2006, Kwon et al 2008, Wang et al 2011, Wen et al 2008, Yano et al 2008. Nonetheless, 17AAG's function in stroke has not been studied although its toxic precursor, geldanamycin, exerts beneficial effects in animal stroke models (Kwon et al 2008, Wen, Li, Zong, Yu et al 2013.…”
Section: Introductionmentioning
confidence: 80%
“…The existing research focuses on the application of GA in cerebral ischemia and brain hemorrhage (Kwon et al 2008;Lu et al 2002;Manaenko et al 2010). These studies collectively determined that Hsp70 induction by GA represses expression of pro-inflammatory markers, reduces infarct size, and downregulates apoptotic pathways in stroke and hemorrhage.…”
Section: Role For Hsps In Therapy and Hsp70-inducing Pharmaceuticalsmentioning
confidence: 99%
“…Geldanamycin has been shown to induce apoptosis [1,5,6,8,9,10,15,20,21,22,23], an effect paralleled by altered gene expression, downregulation of Akt, p38 MAPK activation, mitochondrial depolarization, reactive oxygen species formation, decline of reduced glutathion, lipid peroxidation and caspase activation [5,9,15,20,21]. On the other hand, geldanamycin may counteract neuronal injury, an effect attributed to destabilization of RIP1 protein [4,7,24]. …”
Section: Introductionmentioning
confidence: 99%
“…The benzoquinone ansamycin antibiotic geldanamycin has been shown to inhibit heat shock protein Hsp90 [1,2,3,4,5,6,7,8,9,10,11,12], which prevents stress-induced cellular damage [2], stabilizes various oncogenic kinases [1,7,9,10,12] and influences gene expression e.g. by up-regulating NF-κB [13,14].…”
Section: Introductionmentioning
confidence: 99%